The impact of executive academic experience on corporate ESG performance - Yu Duan; Lei Li; Xindi Yang (Innovation and Green Development)
The implementation of green development and the promotion of harmonious coexistence between humans and nature has become important strategic directions for the development of our country in the new era, and the concept of ESG, which is in line with this development concept, has drawn a lot of attention, according to the report of the 20th Party Congress. In order to conduct an empirical analysis of the effect of executive academic experience on corporate ESG performance, this study chooses data from Chinese non-financial listed businesses from 2009 to 2022 as a sample. The study demonstrates that: (1) Executives' academic backgrounds can improve corporate ESG performance, and the higher the percentage of executives with academic backgrounds in a company, the better for corporate ESG performance. (2) Executive shareholding ratio can weaken the positive relationship between executive academic experience and corporate ESG performance. (3) Executive academic experience can promote corporate ESG performance by inhibiting management's short-sighted behavior. (4) The impact of executive academic experience on business ESG performance increases with lower levels of marketization. This study contributes to existing research on the relationship between executive academic experience and corporate ESG performance, which is important for businesses seeking to improve their ESG performance by hiring academic executives.